2012
DOI: 10.1093/bjsw/bcs101
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Social Work Practices in England: The Early Evidence

Abstract: Social Work Practices (SWPs) were established in England in 2009 to deliver social work services to looked after children and care leavers. The introduction of independent social work-led organisations generated controversy focused on issues such as the privatisation of children's services and social workers' conditions of employment. This paper reports early findings from the evaluation of four of these pilots drawing on interviews with children and young people, staff and local authority and national stakeho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Most SWPs were able to ensure social workers had caseloads of around 15–18 (Stanley et al . 2012b), which increased opportunities for direct contact with children and young people. Although this is not an inevitable consequence of reducing caseloads, other experimental approaches have found that smaller caseloads can result in practitioners spending more time in direct work with children and families, making earlier or more intensive interventions possible (Baginsky et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most SWPs were able to ensure social workers had caseloads of around 15–18 (Stanley et al . 2012b), which increased opportunities for direct contact with children and young people. Although this is not an inevitable consequence of reducing caseloads, other experimental approaches have found that smaller caseloads can result in practitioners spending more time in direct work with children and families, making earlier or more intensive interventions possible (Baginsky et al .…”
Section: Discussionmentioning
confidence: 99%
“…The strengths and weaknesses of the SWP model and the overall findings of the evaluation have been reported elsewhere (Stanley et al . 2012a,b,c). Here, we focus on children's and young people's experience of continuity and staff's accessibility and responsiveness as well as the quality of relationship with practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Here we see a demand for the deregulation of the social work visit through less reliance on prescriptive assessment frameworks and greater engagement with creative and relationship-based practice ( Ruch et al ., 2010 ; Munro, 2011 ). Initiatives such as the ‘Reclaiming Social Work’ Initiative (RSW) in Hackney ( Cross et al , 2010 ), ‘Social Work Practices’ ( Stanley et al , 2012 ) and ‘Systemic Units’ ( Forrester et al , 2013 ) have brought about changes in the delivery of services to children and families' social work that include reduced bureaucratic requirements, decreased caseloads and increased time spent on home visits. Findings from the projects suggest evidence of some positive outcomes from increased opportunities for face-to-face contact, the reduction in the numbers of children coming into care and reduction in staff sickness and turnover rates.…”
Section: Contemporary Discourses and The Social Work Home Visitmentioning
confidence: 99%
“…Social workers are not immune from the influences of market ideologies. This can be seen in how central government are proactively pioneering the privatisation of child protection services for abused and severely neglected children and promoting the concept of 'independent social work practices' albeit ignoring research findings that question their effectiveness (Stanley et al 2012). Similarly the marketisation of social work education marks a shift in their historic role as champions of the oppressed and marginalised (Jones 2014).…”
Section: Impact On Social Workmentioning
confidence: 99%
“…In short, instead of asking what is wrong on the 'production' side of services, the victims are blamed for not being successfully integrated. Rather than address the underlying causes of German social problems, social policy initiatives are concentrating on specific targeted groups who are largely deemed capable of being integrated, while for others the social security system operates as a middle class instrument to enforce values and social/political power co-terminous with this group (Schütte 2013). In short the victims are blamed for not taking up the helping hands of society and the welfare system.…”
Section: Changing Philosophy Of Welfare Production: Re-privatisation mentioning
confidence: 99%